HDGF-related protein-3 is required for anchorage-independent survival and chemoresistance in hepatocellular carcinomas. Issue 3 (5th April 2012) - Xiao, Qianyi; Qu, Kai; Wang, Chenji; Kong, Yahui; Liu, Chao; Jiang, Deke; Saiyin, Hexige; Jia, Fan; Ni, Canrong; Chen, Taoyang; Zhang, Yuanyuan; Zhang, Pingzhao; et al.
Abstract : Objective: Hepatoma-derived growth factor (HDGF)-related proteins (HRPs) comprise a family of six members and are characterised by a conserved HATH domain. Among the family members, HDGF was the first to be identified as a mitogenic factor and shown to play an important role in hepatocellular carcinoma pathogenesis. The aim of the present study is to examine the relevance of HDGF-related protein-3 (HRP-3), another member of the HRP family in hepatocellular carcinoma (HCC). Design: HRP-3 expression in HCC tissues was measured by quantitative reverse transcriptase PCR, western blot and immunohistochemistry analysis. The biological consequences of overexpression and knockdown of HRP-3 in HCC cell lines were studied in vitro and in vivo. Results: Expression of HRP-3 mRNA and protein was shown to be highly upregulated in HCC tissues. While knockdown of HRP-3 by small interference RNAs failed to affect anchorage-dependent growth of HCC cells, it inhibited anchorage-independent growth of HCC cells in vitro and xenograft tumour growth in vivo. Further, knockdown of HRP-3 was shown to sensitise HCC cells to anoikis. Moreover, HRP-3 specifically activated the extracellular-signal-regulated kinase (ERK) pathway without affecting c-Jun N-terminal kinase (JNK), p38, AKT and signal transducer and activator of transcription 3 (STAT3). Importantly, inhibition of the ERK pathway diminished HRP-3-mediated protection of HCC cells from anoikis. Finally, knockdown of HRP-3 was shown to enhance apoptosis of HCC cells induced by multiple chemotherapeutic drugs. Conclusion: These findings indicate that HRP-3 plays an essential role in HCC pathogenesis and suggest that it may serve as a novel prognostic marker and molecular target for development of drugs for treatment of HCC.